The The Influence of Interpersonal Communication, Compensation, and Work Environment on Employee Job Satisfaction at PT Rajawali Nusantara Indonesia (Persero) - Aditya Darmawan Supardi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to describe the relationship of interpersonal communication, compensation, and work environment on employee job satisfaction. The purpose of this research is to explain the influence of interpersonal communication, compensation, and work environment on employee job satisfaction both partially or simultaneously at PT Rajawali Nusantara Indonesia (Persero). The population in this research is all employees of PT Rajawali Nusantara Indonesia (Persero), totaling 267 employees. The sample size in this study consist of 160 employee respondents with a purposive sampling. This research uses a quantitative approach by collecting data through Google Form questionnaires and observation. The analytical method used is the descriptive analysis model and the multiple linear regression analysis model using SPSS version 26 software. The results of this study show that interpersonal communication, compensation, and work environment partially have a significant influence on job satisfaction. Furthermore, interpersonal communication, compensation, and work environment together (simultaneously) have a significant influence on job satisfaction.